Disrupsi Fungsi Media Baru: Sebuah Studi Kasus: Sebuah Studi Kasus - Prayogi, Ichsan Adil; Firdausi, Indrianti Azhar; Oktavia Putri (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
This article discusses the process of disrupting the function of new media. The purpose of this study is to explain how the media has changed its function as a public information service provider to become a company that produces content with profit priority. Using a qualitative research method with a case study approach to a national-scale local media in Banten, the author attempts to describe the disruption of the function of new media. Using Vincent Mosco's political economy theory of communication and a case study on local media with a national network, the author tries to reveal how new media currently functions. The results of our research found that the Radar Banten print media has been used for political or other interests, through titles or news content that has been made, the case that happened to Ratu Atut Chosiyah, the former governor of Banten who was implicated in a corruption case, is one of them. The function of the mass media, which is to provide information to the public, is disrupted because the goals of the mass media are currently more oriented toward group interests and profit. Radar Banten as a mass media that already has a digital version, trying to meet the needs of the public even though it still has many shortcomings, the true function of new media that is carried out by Radar Banten is still in the process of getting to a better stage.